Risk of Diabetic Foot in Diabetic Patients with Peripheral Arterial Disease - Joshi, A. (Kathmandu University Medical Journal, 2020)
Background The prevalence of peripheral arterial disease is higher in diabetic patients. And 11.6% of the patients with diabetic foot ulcer have associated peripheral arterial disease. Objective The main objective of the study is to assess the risk of diabetic foot in diabetic patients with peripheral arterial disease. Method This was a case control study conducted in Bir Hospital, National Academy of Medical Sciences (NAMS). The sample size was 173 out of which cases (diabetic foot) and unmatched controls (diabetics without diabetic foot) were divided in the ratio of 1:2. The Odds Ratio (OR) of peripheral arterial disease in diabetic foot was calculated. The study was conducted after taking ethical clearance from Institutional Review Board of National Academy of Medical Sciences. Result There were 173 participants enrolled in the study. Four were excluded, 55 participants were cases of diabetic foot (cases) and 114 participants were diabetics without diabetic foot (controls). The odds of diabetic foot in patients with peripheral arterial disease was 4.12, p < 0.001. Conclusion The risk of diabetic foot in diabetic patients with peripheral arterial disease was higher as compared to diabetic patients without peripheral arterial disease.